Characterization of Rare Earth Elements in Cassiterite-Associated Minerals in Bangka-Belitung Islands, Indonesia - Syafrizal, Syafrizal; Hede, Arie Naftali Hawu; Rivai, Tomy Alvin; Sihite, Rudy Fernando (Geological Agency, 2024)
Rare earth elements (REEs) are crucial to numerous industries of high-technology as raw materials. The growth of a long-term relationship between REE supply and demand to develop hi-tech industries is becoming tight in the world market, while the mineral supply chain is being distorted by COVID-19. The availability of information and data regarding the REE resource potential and characteristics are interesting research subjects to examine its economic value as alternative sources. This research aims to provide basic information about the existence and characteristics of REEs in cassiterite-associated minerals located in Bangka and Belitung Islands. Fifty-one samples consisting of primary deposits, placer deposits, concentrates, and tailings were collected from the southern Bangka and Belitung region. The samples were analyzed using microscope, x-ray diffraction (XRD), scanning electron microscopy (SEM), electron probe micro-analysis (EPMA), and inductively coupled plasma mass spectrometry (ICP-MS). The results show that the REE-bearing minerals comprised monazite and xenotime. Monazite, the most dominant REE-bearing mineral, contains light REEs (Ce-dominant), while xenotime contains heavy REE (Y-dominant). The results of SEM with energy-dispersive spectroscopy show that monazite contains other LREE (La and Nd), and xenotime also contains other HREE (Dy and Yb). Moreover, zircon and ilmenite can be considered as economical cassiterite-associated minerals that have other mineral inclusion, but have no REE contain.